METAFUNCTION PATTERNS OF THE TOBA BATAK LANGUAGE - Hepnyi Samosir (Universitas Pelita Harapan, 2018)
This study aims at finding out the metafunction patterns of clauses of the Toba Batak Language. The data was gained from the speech of tulang (the mother’s brother) in delivering ulos saput at the Bataknese sari matua (an old person who died but he/she still has children who are unmarried) ceremony. The result shows that 74% of the clauses are patterned with Predicator, Complement, and Adjunct followed by Mood, whereas 26% of them are patterned with Mood followed by Predicator, Complement, and Adjunct. The majority of the clause pattern is Predicator followed by Mood. The most dominant theme is the Marked Topical Theme that reached 73% whereas 26% of them have Unmarked Topical Themes; the rest clause is imperative that has no theme. It can be concluded that clauses in the Toba Batak Language are dominantly patterned by Predicator followed by Mood. The Mood consists of Finite preceding the Subject. Residue itself mostly precedes Mood. The most dominant theme is the Marked Topical Theme in which the theme is not the Subject.BAHASA INDONESIA ABSTRAK: Penelitian ini bertujuan untuk menemukan pola metafunction dalam bahasa Batak Toba. Data peneltian ini adalah klausa-klausa yang disampaikan oleh tulang (saudara laki-laki dari ibu) ketika menyerahkan ulos saput dalam acara saur matua (orang Batak yang meninggal dalam kondisi sudah lanjut usia akan tetapi masih memiliki anak yang belum menikah). Hasil penelitian menunjukkan bahwa 74% klausa terdiri dari Mood yang didahului oleh Predicator, Complement dan Adjunct, dan hanya 26% Mood mendahului Predicator, Complement, dan Adjunct. Kebanyakan klausa dalam bahasa Batak Toba dibentuk dengan pola Predicator yang kemudian diikuti oleh Mood. Theme yang paling dominan adalah Marked Topical Theme yang mencapai 73% sementara 26% merupakan Unmarked Topical Theme; selebihnya merupakan kalimat perintah yang tidak memiliki theme. Dapat disimpulkan bahwa pola klausa dalam bahasa Batak Toba adalah Predicator diikuti oleh Mood. Mood terdiri dari Finite yang mendahului Subjek. Kebanyakan Residue mendahului Mood. Theme yang paling dominan adalah Marked Topical Theme dimana Theme bukan merupakan Subjek.